Effects of Alkaline Solutions on the Structure and Function of Influenza A Virus - Seguchi, Manato; Yamaguchi, Seiji; Tanaka, Mamoru; Mori, Yukihiro; Tsurudome, Masato; Ito, Morihiro (Viruses, 2024)
Influenza A virus (IAV) infection contributes to high annual morbidity and mortality, thus necessitating measures aimed at protecting against the disease. Alcohol-based disinfectants are commonly used to inactivate IAV, but they have several undesirable properties. In search of other means which would inactivate IAV, we focused on the effect of alkaline solutions on IAV. We found the viral infectivity remarkably decreased with treatment of an alkaline solution at pH 12.0 for 1 min, where destruction of the viral spikes was observed using an electron microscope. A more detailed examination revealed that the infectivity of IAV was remarkedly reduced by brief treatment with the alkaline solution at pH 11.75 or above, most likely due to the degradation of viral hemagglutinin protein. These results show that at a high pH, the haemagglutinin protein is degraded, resulting in very rapid inactivation of IAV.